2014
DOI: 10.15613/fijrfn/2014/v1i2/63071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on Quality Evaluation of Composite Flours

Abstract: The present study prepared aims to demonstrate the quality evaluation of roasted and germinated composite flours. Composite flour was prepared with wheat flour, maize flour, green gram flour and groundnut flour. Material balance method was followed to get the required proportions of flours. The samples of first batch were raw and considered as control flour. Second and third batch samples were roasted flour and germinated flour respectively. Roasting and germination were done by the standard methods. Proximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
7
1
0
Order By: Relevance
“…The result shown in Table 1 represents that the ash content is mainly contributed by the SC 9 . The decrease in ash content is also an indicator of the loss of minerals while dehulling 37 . All these results were in agreement with Nazni et al, who reported that processing leads to an increase in protein and carbohydrate values whereas a significant reduction in fat, ash, and moisture content in barnyard millet samples 38 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result shown in Table 1 represents that the ash content is mainly contributed by the SC 9 . The decrease in ash content is also an indicator of the loss of minerals while dehulling 37 . All these results were in agreement with Nazni et al, who reported that processing leads to an increase in protein and carbohydrate values whereas a significant reduction in fat, ash, and moisture content in barnyard millet samples 38 .…”
Section: Resultssupporting
confidence: 90%
“…9 The decrease in ash content is also an indicator of the loss of minerals while dehulling. 37 All these results were in agreement with Nazni et al, who reported that processing leads to an increase in protein and carbohydrate values whereas a significant reduction in fat, ash, and moisture content in barnyard millet samples. 38 The free amino acid is also significantly ( p<0.05) reduced by the different processing methods.…”
Section: Proximate Compositionsupporting
confidence: 91%
“…This is closely related to the findings of Urga et al [12,51], who found 52.4 to 65.2% of carbohydrates in raw GP. Kavitha and Parimalavalli [53] reported a decline in the carbohydrate levels (61.2%) of germinated mungbean flour as compared to raw mungbean flour (65.1%), which supports the findings of the present study. The reason for this reduction may be due to the enzymatic activity of α-amylase that facilitates the synthesis of complex sugars into simple sugars which are used as source of energy in seed germination [65].…”
Section: Discussionsupporting
confidence: 91%
“…Kumitch [52] reported that the fermentation process enhances the protein content in legumes and cereals. An increase in protein content as a result of germination has also been documented by Kavitha and Parimalavalli [53], where the protein content of germinated seeds increased from 21.9 (in raw) to 31.8% in mungbean flour. Similarly, the study reported that germination increased the protein content of germinated groundnut flour, i.e., from 29 to 32%.…”
Section: Discussionsupporting
confidence: 65%
“…During last year's different approaches how to estimate biological value of protein appeared [30]. Fermentation and germination increase the nutritional value of cereals [31][32][33], and the physical and chemical composition is influenced by the growing conditions and processing methods [34].…”
Section: Introductionmentioning
confidence: 99%